The implement of Preoperative 11-items modified Frailty Index and the Surgical Apgar Score might predict the Postoperative Complication Rate in Old Patients undergoing Major Abdominal Surgeries: Observational Prospective Study - Tamer M. Allam; Yehya Shahin Dabour *; Hany A. Shehab (SVU - International Journal of Medical Sciences, 2024)
Background: Frailty is associated with significant diminution of physiologic reserve and worse postoperative (PO) outcomes after major abdominal surgeries (MAS). Objectives are evaluation of the applicability of frailty indices (FI) and the Surgery Apgar score (SAS) for intraoperative events as predictors for the frequency and severity of 30-d PO complications as judged by the Clavien-Dindo classification and PO mortality rate (MR). Patients and methods: 125 patients aged ≥60 years were evaluated preoperatively for frailty using the 11-item and 5-item modified FI (11-mFI & 5-mFI) and during surgery for intraoperative events using SAS. Patients were monitored for 30-d PO for development of complications according to the 5-grade Clavien-Dindo classification. Results: The 11-mFI and 5-mFI detected 85 (68%) and 70 (56%) frail patients, respectively. Among non-frail patients 65% had SAS ≥7, while 77.6% of frail patients had SAS ≤4. Seven non-frail and 30 frail patients developed complications and one non-frail and 5 frail patients died. ROC curve analysis defined high frailty scores as the significant early predictors of SAS≤4 and low SAS with high 5-mFI score as significant predictors for frequency and severity of PO complications. Multivariate Regression analysis defined low SAS and high 5-mFI score as the significant predictors for PO complications and MR, respectively. Conclusion: Low SAS is common among frail patients and both low SAS and high score on FIs might be used as early predictors for PO severe complications and mortality of patients undergoing major abdominal surgeries.